Application of Bulk-Fill Composite to Simplify the Cementation of Indirect Restorations: The COMBO Technique - Giuseppe Chiodera; Riccardo Monterubbianesi; Vincenzo Tosco; Ombretta Papini; Giovanna Orsini; Angelo Putignano (MDPI AG, 2024)
This article proposes a technique to simplify the cementation of indirect restorations by exploiting the advantageous properties of bulk-fill composites (BFCs). The proposed technique consists of using a thin layer of a high-viscosity (HV) BFC in the interproximal margins of the preparation and applying low-viscosity (LV) resin luting agents (RLAs) to the rest of the prepared surface. The application of the HV BFC limits the extrusion of the LV RLAs in the interproximal area, deviating the excesses of LV RLAs only on the vestibular and lingual side. This deviation allows the management and control of the excess material in complicated interproximal spaces, simplifying the cementation procedure of indirect restorations and achieving a reliable final result in terms of removing excess in a safe and repeatable way. This technical report provides an alternative clinical approach for cementing indirect restorations using the consistency and viscosity of different RLAs.